2018
DOI: 10.1177/0011392118783525
|View full text |Cite
|
Sign up to set email alerts
|

When the Internet meets collective action: The traditional and creative ways of political participation in China

Abstract: With the rapid development and wide popularity of the Internet, Chinese people have acquired a revolutionary channel to mobilize collective action and to participate in politics. In order to depict the various factors influencing online collective action in China, and to further explore the dynamic interaction between the Chinese authorities and the public in this new era of collective action, the article attempts to integrate the demand-supply model with relevant studies from both China and abroad to make a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
3
5
0
Order By: Relevance
“…Taking advantage of the professional networks and rapid message dissemination enabled by social media, Chinese seafarers spontaneously participated in collective mobilization in response to unfair treatment. This is consistent with the characteristics of online activism in China as suggested by the previous literature (Tang et al, 2016b;Xue and van Stekelenburg, 2018;Yang, 2009). The two cases demonstrated that the Internet and social media provide social spaces for Chinese seafarers to expand their social networks and form online professional communities, which affords them new resources, such as mutual support and solidarity, to exercise agency.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Taking advantage of the professional networks and rapid message dissemination enabled by social media, Chinese seafarers spontaneously participated in collective mobilization in response to unfair treatment. This is consistent with the characteristics of online activism in China as suggested by the previous literature (Tang et al, 2016b;Xue and van Stekelenburg, 2018;Yang, 2009). The two cases demonstrated that the Internet and social media provide social spaces for Chinese seafarers to expand their social networks and form online professional communities, which affords them new resources, such as mutual support and solidarity, to exercise agency.…”
Section: Discussionsupporting
confidence: 92%
“…It can be understood as "connective action" (Bennett and Segerberg, 2012: 739). This finding is consistent with the major characteristics of online activism in China-spontaneous, unorganized and involving the production and sharing of personally expressive content via social media (Tang et al, 2016b;Xue and van Stekelenburg, 2018;Yang, 2009).…”
Section: Case 2: Fostering Collective Action Onlinesupporting
confidence: 80%
See 1 more Smart Citation
“…Network buzzwords with positive emotions can inspire the spirit of college students and promote their thinking. In contrast, negative emotions damage the thinking of students, causing depression and even desperation, which seriously affects the learning and lives of students ( Weng, 2018 ; Xue and van Stekelenburg, 2018 ).…”
Section: Research Methods and Main Contents Of The Questionnaire Surveymentioning
confidence: 99%
“…In Maoist China (1949China ( -1976, the party-state was a powerful force that could organize and control the lives of people from the womb to the grave (Yao & You, 2018). Due to the thorough penetration of paternalistic government and the lack of formal channels for expressing political appeals, political participation in China has long been considered inefficient and alienated (Xue & van Stekelenburg, 2018). Kent Jennings (1997) points out that political participation in China is frequently characterized as informal and atomistic, driven by particularistic rather than collective goals.…”
Section: Institutional Backgroundmentioning
confidence: 99%